Evaluation of Learning Programs in the Independent Curriculum in Elementary Schools - Anis Maha Tika; Cheen Ceert May; Demina Demina; Zulmuqim Zulmuqim (al-fikrah: Jurnal Manajemen Pendidikan, 2022)
This paper aims to describe the evaluation of learning programs in the independent curriculum in elementary schools. Types of field research research. Data collection techniques that the authors use are observations, interviews, and documentation. Furthermore, the data analysis technique that the authors use as a guide is the data analysis technique according to Miles and Huberman. The steps are from data collection, data reduction, data presentation to conclusions. The results of the study show that the learning program in the independent curriculum has not been implemented optimally. Because of the teacher's difficulties in developing learning tools, including, not being able to read CP (learning achievements) properly, not being able to compile TP (learning objectives) from existing CP (learning achievements), not being able to compile ATP (learning objectives flow) from TP, difficulty developing teaching modules, and independent curricula allowing them to be thematic. So that the results of formative and summative assessments are not in accordance with established standards.